2021
DOI: 10.3390/ijerph182412920
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and Challenges of an English as a Medium of Instruction Course in Taiwan during COVID-19

Abstract: Recently, Taiwan’s higher education has been impacted by COVID-19 and the necessity of English as a Medium of Instruction (EMI). In 2018, the Taiwanese government approved a roadmap for the development of a bilingual nation by 2030. This resulted in a renewed focus on EMI. However, the fluctuating surges of COVID-19 have caused university classes to shift from face-to-face to online. To assess its effectiveness, the current paper describes the quantitative and qualitative experiences and challenges associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 113 publications
0
2
0
Order By: Relevance
“…Moreover, with the impact brought about by the morphosemantic features of the language, they established interventions in helping the students overcome the challenges of switching from "text speech" to formal writing that includes proper spelling. This is not limited to local languages, but is also quite common with other languages besides English and Tagalog, for instance can also be found in Chinese and other dialects (Lin et al, 2021). With this, it aided them regain their communicative skills.…”
Section: Implications For Teaching Practicementioning
confidence: 87%
“…Moreover, with the impact brought about by the morphosemantic features of the language, they established interventions in helping the students overcome the challenges of switching from "text speech" to formal writing that includes proper spelling. This is not limited to local languages, but is also quite common with other languages besides English and Tagalog, for instance can also be found in Chinese and other dialects (Lin et al, 2021). With this, it aided them regain their communicative skills.…”
Section: Implications For Teaching Practicementioning
confidence: 87%
“…This suggests that the use of icebreakers in the Philippine context may be an effective strategy to promote student engagement and participation. Another study by Lin, et al, (2021) investigated the impact of icebreakers on student engagement in a high school classroom in the Philippines. The study found that the use of icebreakers led to increased student engagement, with students reporting higher levels of interest and motivation in the class.…”
Section: Effectiveness Of Icebreakers In the Philippine Contextmentioning
confidence: 99%
“…Students were satisfied with BL because they found it to be an environment conducive to learning, as this modality allowed for the incorporation of interesting content in face-toface classes and effective interaction with the faculty [17]. However, students did not see this incorporation of interesting content in virtual classes [18].…”
Section: Covid-19 Periodmentioning
confidence: 99%
“…Individually, the students highlighted the flexibility they had with BL to organize their time and follow the pace of study that best suited them [17,18,21]. In particular, the fact that they did not have to travel to the university for classes saved them time that they invested in studying or in other activities.…”
Section: Covid-19 Periodmentioning
confidence: 99%